Monetary Policy and Bank Lending: A Natural Experiment from the US Mortgage Market - Carlo Wix; Ulrich Schüwer (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper explores how credit demand affects the pass-through of monetary policy to bank lending. We employ a novel identification strategy based on exploiting exogenous cross-sectional variation in local mortgage credit demand across U.S. counties following the occurrence of large natural disasters. First, we show that large natural disasters cause increased local credit demand in the short-term and reduced local credit demand in the medium-term, which we interpret as intertemporal substitution. We then test whether the effect of monetary policy on bank lending is different for unaffected counties and counties subject to an exogenously reduced credit demand following a natural disaster. We find that credit growth associated with a one percentage point decrease in the federal funds rate is 9 percentage points higher in counties with reduced credit demand relative to unaffected counties. Hence, our results suggest that monetary policy is more effective when credit demand is low.
Keywords: E52; G21; Q54; 330